دور تمكين المرأة في نية ريادة الاعمال لدى طالبات جامعة الوادي مقاربة باستخدام الغابة العشوائية - عبد الرزاق لعويد; سليمة بن عمر (جامعة الوادي University Of Eloued, 2025)
تهدف هذه الدراسة تحليل أثر تمكين المرأة من خلال أبعاده المتعددة النفسية والاجتماعية، والاقتصادية والتعليمية على نية ريادة الأعمال لدى طالبات جامعة الوادي بالجزائر استندت الدراسة إلى منهجية كمية، تم تنفيذها عبر استبيان إلكتروني وزع على عينة طبقية قصدية شملت 550 طالبة من مختلف التخصصات والمستويات الأكاديمية، وتم تحليل البيانات باستخدام خوارزميات أشجار التصنيف والانحدار (CART) والغابات العشوائية (Random Forest). أكدت الدراسة أن العوامل النفسية، ولا سيما التمكين النفسي والكفاءة الذاتية والدوافع الريادية، هي الأكثر تأثيرا في تشكيل نية ريادة الأعمال لدى الطالبات، تليها البيئة الجامعية والخبرة التعليمية والتدريبية. في المقابل، تبين أن العوائق الاجتماعية والبيئية مثل الأعراف، وصعوبة التمويل، وضعف الدعم المؤسسي، تؤثر سلبا على النية الريادية، وإن كان تأثيرها أقل من العوامل النفسية والدافعية. كما كشفت النتائج عن محدودية تأثير المتغيرات الديموغرافية (العمر، الحالة الاجتماعية، التخصص مقارنة بالعوامل النفسية والسلوكية. خلصت الدراسة إلى أن تعزيز برامج التمكين النفسي والتدريب الريادي داخل الجامعات، وتطوير البيئة الجامعية لتكون أكثر دعما للمبادرات النسائية، وتوفير الدعم المالي والمؤسسى، يمثلان ركائز أساسية لتعزيز ريادة الأعمال النسائية في البيئة الجامعية الجزائرية، بما يسهم في تحقيق التنمية الاقتصادية والاجتماعية المستدامة. This study analyzed the impact of women's empowerment across its multiple dimensions-psychological, social, economic, and educational on the entrepreneurial intentions of female students at El Oued University in Algeria. The study relied on a quantitative methodology, implemented through an electronic questionnaire distributed to a stratified, purposive sample of 550 female students from various disciplines and academic levels. The data were analyzed using Classification and Regression Trees (CART) and Random Forest algorithms. The study confirmed that psychological factors, particularly psychological empowerment, self-efficacy, and entrepreneurial motivation, are the most influential in shaping female students' entrepreneurial intentions, followed by the university environment and educational and training experience. Conversely, social and environmental barriers, such as norms, funding constraints, and weak institutional support, negatively impact entrepreneurial intentions, although their impact is less than that of psychological and motivational factors. The results also revealed limited influence of demographic variables (age, marital status, specialization) compared to psychological and behavioral factors. The study concluded that strengthening psychological empowerment and entrepreneurship training programs within universities, developing the university environment to be more supportive of women's initiatives, and providing financial and institutional support are essential pillars for promoting women's entrepreneurship in the Algerian university environment, contributing to achieving sustainable economic and social development.
Keywords: تمكين المرأة; ريادة الأعمال نية ريادية; طالبات الجامعة; أشجار التصنيف والانحدار; Women's Empowerment; Entrepreneurship. Entrepreneurial Intention; Female University Students; Classification and Regression Trees (CART